2017
DOI: 10.1128/genomea.01524-16
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Streptococcus iniae 89353, a Virulent Strain Isolated from Diseased Tilapia in Taiwan

Abstract: Streptococcus iniae 89353 is a virulent strain isolated from diseased tilapia in Taiwan. The full-genome sequence of S. iniae 89353 is 2,098,647 bp. The revealed genome information will be beneficial for identification and understanding of potential virulence genes of Streptococcus iniae and possible immunogens for vaccine development against streptococcosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…One of these ~7 kb discarded contigs encoded an rRNA region (5S, 16S and 23S genes in tandem with an intervening cluster of tRNA genes). Subsequent reassembly and visualization of mapped raw reads indicated that the additional rRNA contig could be placed in three of the five rRNA operon locations to form an ~13 kb putative tandem duplication of 5S, 16S and 23 rRNA genes as seen in the 89 353 genome [ 47 ]. Closer examination of the read pileup for the ~7 kb rRNA contig revealed that the tandem duplication was not well supported by overlapping reads (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these ~7 kb discarded contigs encoded an rRNA region (5S, 16S and 23S genes in tandem with an intervening cluster of tRNA genes). Subsequent reassembly and visualization of mapped raw reads indicated that the additional rRNA contig could be placed in three of the five rRNA operon locations to form an ~13 kb putative tandem duplication of 5S, 16S and 23 rRNA genes as seen in the 89 353 genome [ 47 ]. Closer examination of the read pileup for the ~7 kb rRNA contig revealed that the tandem duplication was not well supported by overlapping reads (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, during the preparation of this paper, a PacBio complete genome was published for S. iniae 89 353 (accession: CP017952), which has an identical rRNA arrangement to QMA0248 except that one rRNA locus encodes an ~7 kb tandem duplication (i.e. six loci in total) [47]. Such intraspecies variation in the number of rRNA genes (and tRNA genes) is not uncommon in bacteria (including streptococci) [48,49], and prompted us to investigate further.…”
Section: Genomic Features Of S Iniae Qma0248mentioning
confidence: 99%
“…Zebrafish embryos cultured until they became one-month-old juveniles were used for an RHS toxicity assay. The clinical pathogen methicillin-resistant Staphylococcus aureus (MRSA) was kindly provided by Dr. Huang et al [25], and Streptococcus iniae was kindly provided by Dr. Gong et al [26]. The foodborne pathogens Escherichia coli BCRC11634, Staphylococcus aureus BCRC12991, Salmonella typhimurium BCRC12947, and Listeria monocytogenes BCRC14932; clinical pathogen Pseudomonas aeruginosa BCRC12902; and plant pathogen Burkholderia gladioli BCRC13899 were purchased from the Bioresource Collection and Research Center (BCRC), Food Industry Research and Development Institute, Taiwan.…”
Section: Fish and Bacterial Strainsmentioning
confidence: 99%
“…Regardless of the PCR supermix used, the newly designed multiplex qPCR assay targeting Fno , S. iniae, and S. agalactiae was found to be repeatable and reproducible, with a linear dynamic range covering at least five orders of magnitude. Based on estimated genome sizes of 1.9 Mb for Fno (Figueiredo et al, ), 2 Mb for S. iniae (Gong et al, ), and 2 Mb for S. agalactiae (Mainardi et al, ), the limit of sensitivity for each assay was approximately 20, 8, and 20 genome equivalents, respectively. Each assay was specific to its respective target, with no evidence of cross‐reactivity from nontarget organisms (Figure ; Table ).…”
Section: Resultsmentioning
confidence: 99%